D-dimer and myocardial infarction in patients with COVID-19: a systematic review and meta-analysis (Research, Society and Development, 2022)
This study aimed to identify current evidence on the association between D-dimer levels and the occurrence of myocardial infarction (MI) in patients with COVID-19. For this, a systematic review was performed, using the following databases: PubMed, Embase, Web of Science, Scopus, Livivo, and Google Scholar. We applied the following inclusion criteria: studies that investigated the association between COVID-19 and MI; and studies with D-dimer data. We exclude review studies, with animal models, in vitro, and case reports. For the synthesis of the results, we used a standardized mean difference (SDM) meta-analysis to pool the D-dimer data. Thus, 06 studies were included in this systematic review presenting two methodological approaches: 02 studies investigated cases of COVID-19, seeking to identify the development of myocardial infarction; and the other 04 studies evaluated patients with myocardial infarction to determine those patients who had presented COVID-19. The SDM results of the meta-analyses for each approach were respectively: 0.86 [95% CI (0.63 to 1.08), p < 0.0001, favoring the group that developed MI] and 2.08 [95% CI (-0.01 to 4.17), p=0.0512, favoring those who had presented COVID-19]. Therefore, in this systematic review, we demonstrate an association between D-dimer levels in patients with COVID-19 and myocardial infarction. However, these results showed very low evidence in the GRADE classification, which indicates the need for more studies on the topic.